PENGARUH FINANCIAL DISTRESS, MANAJEMEN LABA DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA PERIODE 2017 - 2021 - Miswaty Miswaty; Liza Syah Putri; Rihfenti Ernayani; Ika Makherta Sutadji (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2023)
This study aims to examine Financial Distress, Earning Management, and Leverage on Tax Avoidance the coefficient of determination, partially, and simultaneously. The population in this study were mining companies listed on the Indonesia Stock Exchange 2017-2021. After purposive sampling was carried out, there were 18 companies that met the criteria. Data analysis techniques using multiple regression analysis method, because the data in the study in the form of nominal data. The results showed that Financial Distress (X1) has a negative and significant effect on the Tax Avoidance of the company. While Earning Management (X2) and Leverage (X3) has no significant effect on the Tax Avoidance of the company.